(untitled) (The International Journal of Engineering & Information Technology (IJEIT), 2024)
Abstract- information security management model through the data life cycle is a model that can help us to follow and understand the strategy life of the institution and determining all probabilities of threats and vulnerabilities of occurrence and outcomes through implementing it within the institution. The data life cycle has been chosen that the data life cycle management enables us to understand our data, which is an extremely valuable business asset and which must be managed properly, to ensure business success and regulatory compliance. Understanding data life cycle management means to classify and determine rules, responsibilities and IT needed and determine the requirement to business targets done in the best way, here we can say that it is the way to find out the weakness in the data process and helping us to determine security technical requirement and provide the security policy.